Early Reversible Ischemia of Femoral Head Epiphysis in Piglets on Gadolinium-enhanced MRI： An experimental study - 李小明 胡军武 郑红伟 唐立华 徐安辉 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
Summary： The purpose of this study is to demonstrate if Gadolinium-enhanced MRI can detect early reversible ischemia of the femoral head epiphysis caused by hip hyper-abduction in piglets. Between 3 and 6 h consistent hyper-abduction, gadolinium-enhanced MRI was performed in 20 femoral heads of 10 piglets. After completion of MRI scan, the piglets were allowed to ambulate freely for 1 or 7 days and re-imaged. The enhanced-MRI results of epiphyseal and physeal cartilage and the secondary center of ossification were observed. MRI appearances and histological findings were compared. On Gadolinium-enhanced MRI, decreased or absent enhancement was seen in 14 cartilaginous epiphyses of all 20 femoral heads. Reperfusion was completed in 10 of 14 femoral heads after one day of ambulation and in the rest 4 after 7 days of ambulation. Gadolinium-enhanced MR/can identify early ischemia and its reversal of the capital femoral epiphysis induced by hip hyper-abduction.